Pohlia chilensis (Mniaceae), an Afro-American moss - Suarez, Guillermo Martin (2008)
Pohlia clavicaulis from Bolivia and Pohlia emergens from Argentina are reduced to synonymy under Pohlia chilensis (Mont.) A. J. Shaw. This Andean species, characterized by its polysetous condition, is also recorded for the first time from Africa